Genotype-phenotype association of PITX2 and FOXC1 in Axenfeld-Rieger syndrome. (January 2023) - Zhou, Lin; Wang, Xiaoli; An, Jingqi; Zhang, Yao; He, Mengxia; Tang, Li
Abstract: PITX2 and FOXC1 are the most common pathogenic genes associated with Axenfeld-Rieger syndrome (ARS). In this study, we aimed to explore the variation spectrum of PITX2 and FOXC1 and their associated phenotype based on data from our study and previously reported literatures. Whole exome sequencing was performed on eight probands in our study. Multistep bioinformatic and co-segregation analyses were performed to detect pathogenic variants. Genotype-phenotype correlations of PITX2 and FOXC1 and the differences between them were determined. We detected three variants of FOXC1 and two variants of PITX2 in five unrelated families with ARS. Macular retinoschisis had been observed in AR1 with variant in PITX2 and it is not reported before. Additionally, a review of published literature and our study led to the identification of 593 families with variants of PITX2 or FOXC1, including 316 families with heterozygous variants in FOXC1, 251 families with heterozygous variants in PITX2, 13 families with variants in double genes, seven families with homozygous or compound heterozygous variants in FOXC1, and six families with variants in ADAMTS17, PRDM5, COL4A1 or CYP1B1. Significant differences were observed between the prevalence of missense and in-frame, truncation, and large deletion variants in PITX2 (32.00%, 42.67%, and 25.33%, respectively) and FOXC1 (34.49%, 35.13%, 30.38%, respectively) (p = 1.16E-43). Enrichment and frequency analyses revealed that missense variants were concentrated in the forkhead domain of FOXC1 (76.14%) and homeodomain of PITX2 (87.50%). The percentage of Caucasians with variants in FOXC1 was significantly higher than that of PITX2 (p = 2.00E-2). Significant differences between PITX2 and FOXC1 were observed in glaucoma (p = 3.00E-2), corectopia (p = 3.050E-6), and polycoria (p = 5.21E-08). Additionally, we observed a significant difference in best-corrected visual acuity (BCVA) between FOXC1 and PITX2 (p = 3.80E-2). Among all the family members with PITX2 or FOXC1 variants, the prevalence of systemic abnormalities was significantly higher in PITX2 than in FOXC1 (89.16% vs. 58.77%, p = 5.44E-17). In conclusion, macular retinoschisis as a novel phenotype had been observed in patient with variant in PITX2 . Significant differences were detected in phenotypes and genotypes between PITX2 and FOXC1 . Highlights: Macular retinoschisis are detected in PITX2. PITX2 and FOXC1 are the most common genes for ARS. Missense concentrated on the forkhead domain of FOXC1 and homeodomain of PITX2. The phenotypes and genotypes significantly differ between PITX2 and FOXC1.